Maximal strength and power, muscle mass, endurance and serum hormones in weightlifters and road cyclists - Izquierdo, M.; Ibanez, J.; Hakkinen, K.; Kraemer, W. J.; Ruesta, M.; Gorostiaga, E. M. (Journal of Sports Sciences, 2004)
Maximal strength, power, muscle cross-sectional area, maximal and submaximal cycling endurance characteristics and serum hormone concentrations of testosterone, free testosterone and cortisol were examined in three groups of men: weightlifters (n = 11), amateur road cyclists (n = 18) and age-matched controls (n = 12). Weightlifters showed 45-55% higher power values than road cyclists and controls, whereas the differences in maximal strength and muscle mass were only 15% and 20%, respectively. These differences were maintained when average power output was expressed relative to body mass or relative to muscle cross-sectional area. Road cyclists recorded 44% higher maximal workloads, whereas submaximal blood lactate concentration was 50-55% lower with increasing workload than in controls and weightlifters. In road cyclists, workloads associated with blood lactate concentrations of 2 and 4 mmol.l-1 were 50-60% higher and occurred at a higher percentage of maximal workload than in weightlifters or controls. Basal serum total testosterone and free testosterone concentrations were lower in elite amateur cyclists than in age-matched weightlifters or untrained individuals. Significant negative correlations were noted between the individual values of maximal workload, workloads at 2 and 4 mmol.l-1 and the individual values of muscle power output (r = -0.37 to -0.49), as well as the individual basal values of serum total testosterone and free testosterone (r = -0.39 to -0.41). These results indicate that the specific status of the participants with respect to training, resistance or endurance is important for the magnitude of the neuromuscular, physiological and performance differences observed between weightlifters and road cyclists. The results suggest that, in cycling, long-term endurance training may interfere more with the development of muscle power than with the development of maximal strength, probably mediated by long-term cycling-related impairment in anabolic hormonal status.